MENDONGENG SEBAGAI MEDIA PENGAJARAN - Billy Suandito (Jurnal Abdimas Musi Charitas, 2017)
The teaching and learning are a process that causes the activity of teachers and students do an activity together or work together and interact and interact to achieve the learning objectives. So that the learning objectives can be achieved, a teacher must be able to prepare the components supporting learning. One of them with the use of instructional media storytelling as a means of learning of students in the school. Storytelling can integrate media, teachers can optimize the message contained in a story, as well as to stimulate thought, feeling, hearing, vision, and interests of students during the learning process takes place. Learning through storytelling is learning that is fun, delivered with an atmosphere of warmth. The method used in service activities in SD Xaverius IV Palembang simulation method, discovery, and frequently asked questions. As a result, all students receive instruction at a time of refreshment in learning through storytelling.